Total Quality Management (TQM) in Islamic Educational Institutions - Wafa, Ainul (Tadibia Islamika: Journal of Holistic Islamic Education, 2022)
The teacher's task is to give instructions and guide students for more progressive knowledge, skill, and self-constructivism to develop their potential. This article's purpose is to outline TQM's role in Islamic education institutions. This research uses a qualitative method through library research or data collection from several literatures that discuss the concept of Total Quality Management in educational institutions and implementation in Islamic education. The results of this study are expected (1) Improve quality and competitiveness for outputs (graduates) with an indicator of the competence of both intellectual and skill and intelligent mind, spiritual, emotional and balanced between hard skills and soft skills as well as active, creative and innovative and adaptive to the development of science and technology and employment. (2) Institutions of Islam that the implications can improve students' competencies that form the civilized man who is aware of the rights and obligations to God, on him and the environment. (3) creating integrated quality; integrated quality is not something that happens suddenly and appears before the teachers, employees and the headmaster. Quality must be planned. There is trilogy of quality, namely quality planning, quality control, and quality improvement. Because TQM prioritizes the integration of all functions and processes and empowers and involves all elements in the educational institution. TQM must be applied continuously and continuously in order to achieve a religious education, which gives satisfaction to students, parents and society.